Partisipasi Masyarakat Dalam Kebijakan Pendidikan: Urgensi, Tantangan, Dan Strategi Penguatannya - Aril Deo Saputra; Muhammad Bahrul Musthofa; Anisah Najwa Mumtaza; Qoidatul Ghurril Muhajjalin (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
Community participation is an important factor in supporting the success of educational policies. This article aims to analyze the urgency of community participation in educational policy, identify the challenges encountered, and examine strategies for strengthening such participation. This study employs a library research method with a descriptive qualitative approach through the analysis of relevant literature sources. The findings indicate that community participation plays a significant role in improving educational quality, strengthening accountability, and supporting the development of more democratic educational policies. However, community participation still faces several challenges, including low public awareness, limited access to information, socio-economic constraints, and weak communication between schools and communities. Therefore, efforts to strengthen community participation are needed through increased transparency, optimization of school committee roles, community empowerment, the utilization of digital technology, and collaboration among government, schools, families, and communities to achieve quality and sustainable education.